2017
DOI: 10.1016/j.memsci.2016.12.058
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feed spacer geometry on membrane performance and concentration polarisation based on 3D CFD simulations

Abstract: Feed spacers are used in spiral wound reverse osmosis (RO) membrane modules to keep the membrane sheets apart as well as to enhance mixing. They are beneficial to membrane performance but at the expense of additional pressure loss. In this study, four types of feed spacer configurations are investigated, with a total of 20 geometric variations based on commercially available spacers and selected filament angles. The impact of feed spacer design on membrane performance is investigated by means of three-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 44 publications
(89 reference statements)
3
65
0
Order By: Relevance
“…The region adjacent to the transverse filaments wall has much higher concentrations [18]. Boram et al [19] compared the water flux in four classic types of feed spacer configurations, which included nonwoven, partially woven, middle-layer, and fully woven spacers, and showed concentration contours near the transverse filaments using COMSOL Multiphysics. Van Gauwbergen et al [20] reported the same situation using potassium and calcium chloride as tracers in the experimental research.…”
Section: Feed Spacer Design-related Problemmentioning
confidence: 99%
“…The region adjacent to the transverse filaments wall has much higher concentrations [18]. Boram et al [19] compared the water flux in four classic types of feed spacer configurations, which included nonwoven, partially woven, middle-layer, and fully woven spacers, and showed concentration contours near the transverse filaments using COMSOL Multiphysics. Van Gauwbergen et al [20] reported the same situation using potassium and calcium chloride as tracers in the experimental research.…”
Section: Feed Spacer Design-related Problemmentioning
confidence: 99%
“…A limitation of this approach is the very long computational time required to solve the model equations, thus making the tool unsuitable for practical applications . Recently, Gu et al reported that simulation of a three‐dimensional periodic domain of a spacer‐filled channel takes more than 3 hr by a RAM‐96GB workstation . So a number of simplified Nernst‐Planck and Maxwell‐Stefan mathematical models have been developed to study the mass transfer through ion‐exchange membranes .…”
Section: Introductionmentioning
confidence: 99%
“…12 Recently, Gu et al reported that simulation of a three-dimensional periodic domain of a spacerfilled channel takes more than 3 hr by a RAM-96GB workstation. 26 So a number of simplified Nernst-Planck and Maxwell-Stefan mathematical models have been developed to study the mass transfer through ionexchange membranes. [27][28][29] However, the discrepancy between theoretical results and experimental data always occurs due to unreasonable assumption in transport modeling.…”
Section: Introductionmentioning
confidence: 99%
“…In the feed channel of membrane system spacers influence the flow regime by imposing mixing and increased back diffusion of solutes from the membrane surface into the bulk solution. The use of feed spacers increases mass transfer [11] by reducing the CP [12], but also enhances the development of fouling in the feed channel [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%